1978
DOI: 10.1210/endo-103-4-1253
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Luteinizing Hormone Biosynthesis and Release by Gonadotropin-Releasing Hormone, Cycloheximide, and Actinomycin D*

Abstract: In the first experiment, the influence of synthetic gonadotropin-releasing hormone (GnRH) on the time course of [3H]glucosamine ([3H]GA) and [14C]alanine ([14C]A) incorporation into LH by quartered rat anterior pituitary glands and the sequence of release of radiolabeled and total immunoreactive LH (IR-LH) was investigated. Radiolabeled LH was measured by immunoprecipitation and total IR-LH was measured by RIA. After lag periods of 5 and 20 min, respectively, incorporation of [14C]A and [3H]GA into tissue LH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…One possible explanation of this unexpected synergism between calmodulin antagonists and TPA is that cytosolic Ca2+ is made more available for activation of protein kinase C during the inhibition of calmodulin by the antagonist [31][32][33]. It is possible that the inhibition of PDE by calmodulin antagonists increases the cyclic nucleotides which have been implicated in the stimulation of gonadotropin synthesis [9,34]. However, neither cyclic AMP nor cyclic GMP appears to participate in LH release within a couple of hours [35].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation of this unexpected synergism between calmodulin antagonists and TPA is that cytosolic Ca2+ is made more available for activation of protein kinase C during the inhibition of calmodulin by the antagonist [31][32][33]. It is possible that the inhibition of PDE by calmodulin antagonists increases the cyclic nucleotides which have been implicated in the stimulation of gonadotropin synthesis [9,34]. However, neither cyclic AMP nor cyclic GMP appears to participate in LH release within a couple of hours [35].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first demonstration that the phase II release of TSH involves protein synthesis. Though the protein synthesisdependent release in LH has been reported (Pickering and Fink, 1976 ;Kercret and Duval, 1978 ;Liu and Jackson, 1978 ;Bourne and Baldwin, 1980), the significance of the dependency in the dynamics of the hormone secretion is still unknown. Since the shift from phase I to phase II release occurs before complete depletion of a previously prepared-releasable pool, it is possible that the phase II release in an early period is also consuming the releasable pool that had been prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Since the profile of the biphasic release caused by a maximally effective concentration of TRH was different from that by high K+ (60 mM) solution, there seems to be a specific action of TRH related to the biphasic release (Shiota et al, 1984). Though protein synthesis is theoretically expected to play an important role in the second-phase release, as shown in the case of LH (Pickering and Fink, 1976 ;Kercret and Duval, 1978 ;Liu and Jackson, 1978 ;Bourne and Baldwin, 1980), the relation of the first and the second release of TSH in connection with protein synthesis is poorly understood.…”
Section: During Constant Stimulationmentioning
confidence: 99%
“…in the presence of 10 ng/m l TRH (Tanabe Pharmaceutical Co., Osaka, Japan), cycloheximide (25 jig/ml), or actinomydn D (25 ug/ml). Although in the previous studies varying doses (ranging from 0.1 to 100 pg/m l) of cycloheximide and actinomydn D were used to inhibit pituitary protein synthesis [16,17,23], we employed 25 pg/m l of each drug, a dose suita ble for significant inhibition o f protein synthesis [25,26]. In the present study, cycloheximide and actinomydn D at doses o f 25 pg/m l were observed to significantly inhibit [l4C)alanine incorporated into pituitary protein which was precipitated by trichloroacetic acid (3 h incubation, the TRH-added group, 22.7 ± 1.7; the TRH + cycloheximide-added group, 2.1 ± 0.4; the TRH + actinomydn D-added group, 13.3 ± 1.1; 6 h incubation, the TRH-added group, 31.4 ± 3.7; the TRH + cycloheximide-added group, 1.8 ± 0.1; the TRH + actinomycin Dadded group, 19.1 ± 1.4 x 10-3 dpm /A P, n = 5 in each group).…”
Section: Methodsmentioning
confidence: 99%
“…This drug was also found to be unable to change gonodotropin-releasing hormone (GnRH)-stimulated LH release [23], It was observed that actinomycin D did not inhibit [3H]glucosamine-incorporation into pituitary hormones in the presence ofTRH and GnRH. while cycloheximide, a drug inhib iting protein synthesis [24], significantly reduced its incorpora tion [25,26]. These observations were interpreted to support the possibility that messenger RNA may not contribute to the car bohydrate synthesis of glycoprotein hormone in the short-termincubation, although protein synthesis is required for glycosyla tion of pituitary hormone.…”
mentioning
confidence: 93%